Why the North Won the Vietnam War
256 p.
Keywords: In this new collection of essays on the Vietnam War, eminent scholars of the Second Indo-china conflict consider several key factors that led to the defeat of the United States and its allies. The book adopts a candid and critical look at the United State's stance and policies in Vietnam, and refuses to condemn, excuse, or apologize for America's actions in the conflict. Rather, the contributors think widely and creatively about the varied reasons that may have accounted for the United State's failure to defeat the North Vietnamese Army, such as the role played by economics in America's defeat. Other fresh perspectives on the topic include American intelligence failure in Vietnam, the international dimensions of America's defeat in Vietnam, and the foreign policy of the Democratic Republic of Vietnam. None of the essays have been previously published, and all have been specifically commissioned for the book by its editor, Marc Jason Gilbert.